Implementasi PSAK Pasal 65 dan Peraturan Pajak di Indonesia Pada Laporan Keuangan Konsolidasi yang Terdaftar di BEI - Septiana Putri Pangestu; Lisna Miranda; Melinda Dyah Astuti; Endang Kartini Panggiarti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Consolidated report is an important report for companies that purchase or merge from other companies. The purpose of this study is to provide an overview of how the implementation of PSAK 65 and tax regulations in Indonesia on the consolidated financial statements listed on the IDX. The research method used in this research is literature review of articles or previous research. The data used in this study are secondary data from articles obtained from the Google Scholar database and consolidated financial statements published on the IDX. Based on the results of the analysis, it is known that every company that acquires another company has issued consolidated financial statements and implemented PSAK 65 and the existing tax regulations in Indonesia.